Improvement Productivity Menggunakan Metode Time And Motion Study Pada Area Line F PT KHI - Aditya Aprodicto Bestafirli; Joumil Aidil Saifuddin (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
PT KHI is a company operating in the food and beverage industry in Indonesia. In production activities there are many factors that can hinder performance productivity. Worker productivity is a value that cannot be seen directly except through a calculation process, so the worker productivity value is calculated from the company PT KHI. This research was carried out in the Production department using the Time and Motion Study method with a Lean Manufacturing approach, namely waste or extravagance to increase labor productivity in the Production department area. This time it was carried out directly by means of field observation. So that primary data is obtained. The results were obtained in the form of recommendations for improvement, namely: adjusting the total headcount in the line F area from previously 7 headcounts to 6 headcounts and moving several tasks from the carton sealer operator to each operator in the packing area of ​​line F, then classifying them into 3 headcounts for the packing section and 3 headcounts for the packing section. . It can be concluded from the results of this research that one type of waste is eliminated, namely adjusting the number of operators in the packing line F area so that before the improvements, labor productivity is 71.71% on line F and after labor productivity is 83.63%. By making improvements, cost savings of IDR 4,515,133 were obtained for 26 working days.